Exploring Business Ethics and Social Responsibility in Tourism Organizations Amid Environmental Changes - Isabell, Virginie; Gregor, Irena (Journal Economic Business Innovation, 2024)
Purpose: The paper examines the concepts of business ethics and social responsibility in tourism organizations and how these concepts affect their actions and strategies in an era of rapid environmental changes in France. The goal of the study is to investigate the role of ethical operations and social responsibility in organizational performance and sustainability in the tourism industry.Method: A mixed-methods approach including qualitative interviews with key tourism industry leaders and quantitative surveys of employees from different organizations. SmartPLS was used to do Structural Equation Modeling (SEM) analysis, which means that the company included business ethics, social responsibility, managerial behavior, and organizational outcomes in the analysis of statistical significance.Findings: The study finds a positive influence of business ethics on competitive advantage in tourism organizations and an encouraging effect of the practice of social responsibility on customer loyalty. In addition, managerial ethical behavior importantly mediates the connection of organizational culture to employee performance. Impacts of Environmental Changes on Ethical Practices and Organizational Sustainability Relationship.Novelty: This study makes a novel contribution to the field by examining the emerging relationship between business ethics, social responsibility and environmental transformations, specifically in the context of the tourism sector in France. It underscores the importance of ethical leadership and the incorporation of sustainable practices in tourism businesses.Implications: The implications derived from the findings imply that tourism organizations should focus on ethical training, social responsibility in strategies, and sustainability in views of environmental changes for their competitiveness. This information shall be used by the policy makers and leaders of the Industries to prepare more ethical and responsible tourism element